Influence of Gender, Education Level, Alcohol Etiology, and Serum Sodium Levels on Delayed Neurocognitive Recovery in Patients Undergoing Living Donor Liver Transplant Surgery in Early Postoperative Period: A Single-Center, Prospective, Observational Study - Deepak Mishra; Natasha Khullar Kumar; Ramneek Kaur; Vijay Vohra; Neerav Porwal; Ajit Bhardwaj (Indian Journal of Transplantation)
Background and Aims: Postoperative cognitive dysfunction has been known to be associated with liver transplantation. This study aimed to assess the effect of gender, education levels, alcohol etiology, and serum sodium levels using four different tests. Materials and Methods: Thirty-five adult patients undergoing elective living donor liver transplant were divided into male/female, school educated (SE)/college educated (CE), alcohol-related liver disease (ALD)/non-ALD (NALD), and hyponatremia/normonatremia. For comparison of each variable, four different cognitive domains (global cognitive function, executive function, for intelligence, immediate/distant recall, and memory) were tested 24–48 h presurgery and 12–14 days postoperatively. Results: Among the groups, a higher proportion of male patients, SE patients, ALD patients, and hyponatremia patients had impairment in the majority of tests preoperatively as well as postoperatively. In SE (when compared to CE) patients, executive functions had a statistically significant increase in the number of patients with impairment preoperatively. In hyponatremia (when compared to normonatremia) patients, global cognitive and executive functions had a statistically significant increase in number of patients with impairment preoperatively. CE, NALD, and normonatremia group had statistically significantly increased number of patients with impaired executive functions postoperatively (when compared pre- versus postoperatively) than SE, ALD, hyponatremia group, respectively. Conclusion: Lower education level, alcohol etiology, and hyponatremia had an emphatic effect on cognitive function in the baseline as well as postoperative period (statistically significant in SE and hyponatremia groups). Executive domain of cognitive functions was most frequently affected; and there was a statistically significant increased number of patients with impairment in this function in the early postoperative period in CE, NALD, and normonatremic patients.